Low gamma-glutamyl transpeptidase levels at presentation are associated with severity of liver illness and poor outcome in biliary atresia - Sun, Song; Zheng, Shan; Shen, Chun; Dong, Rui; Dong, Kuiran; Jiang, Jingying; Yang, Yifan; Chen, Gong (Frontiers in Pediatrics, 2022)
Objective To investigate the clinical features and prognosis of biliary atresia (BA) with normal or minimally elevated gamma-glutamyl transpeptidase(GGT). Methods The clinical data of patients with BA in our hospital between 2012 and 2017 were retrospectively studied. The patients were divided into low-GGT group(GGT≤300IU/L) and high-GGT group(GGT>300IU/L) according to the preoperative GGT level. The perioperative clinical parameters, the postoperative jaundice clearance within 6 months and the 2-year native liver survival were compared among the groups. Results A total of 1,998 children were included in this study, including 496 in the low-GGT group and 1502 in the high-GGT group. The ages and weights at surgery in the low-GGT group were significantly lower than those in the high-GGT group (64.71±21.35 vs. 68.64±22.42 days,P=0.001; 4.67±1.03 vs. 4.89±0.98 kg,P<0.001). The levels of serum ALP, ALT and AST in the low-GGT group were significantly higher than those in the high-GGT group before and 2 weeks after surgery (ALP: 647.52±244.10 vs. 594.14±228.33U/L,P<0.001; ALT: 119.62±97.14 vs.96.01±66.28U/L,P<0.001; AST: 218.00±173.82 vs. 160.71±96.32U/L;P<0.001). The INR of low-GGT group was higher than that of the high-GGT group (1.05±0.34 vs. 0.98±0.20, P<0.001), while FIB was lower than the high-GGT group (2.54±0.67 vs. 2.73±1.44g/L; P=0.006). The decreasing amplitude of TB and DB within 2 weeks after surgery in the low-GGT group was smaller than those in the high-GGT group (TB:51.62±71.22 vs. 61.67±53.99 umol/L,P=0.003; DB:33.22±35.57 vs. 40.20±35.93 umol/L,P<0.001). The jaundice clearance rate in the low-GGT group was significantly lower than that in the high-GGT group at 1, 3 and 6 months after surgery (17.70% vs. 26.05%; 35.17% vs. 48.58%; 38.62% vs. 54.64%, P<0.001). Additionally, the 2-year native liver survival rate in the low-GGT group was significantly lower than that of the high-GGT group (52.5% vs. 66.3%, P<0.001 HR 1.80, 95% CI 1.38-2.33). Conclusion Compared to patients with high GGT, patients with normal or minimally elevated pre-operative GGT in BA were found to have poorer pre-operative liver function parameters, and post-operatively had lower jaundice clearance rates and worse 2 year native liver survival. This suggests a lower GGT at presentation in biliary atresia could be a sign of more severe liver injury.